STUDI KELAYAKAN NERACA MESIN PACKING PADA PENGANTONGAN SEMEN DI PT. SEMEN TONASA - Haris Tehuayo; Sriwati Sriwati; Farida Farida; Sajiah Sajiah (Elektrika Borneo, 2019)
From year to year technological improvement is guite significant, it is also marked by the emergence of various kinds of technology, especially the balance sheet. In the balance sheet needs calibration. Calibration is usually done by comparing standards that are linked to national standards as well as international standards and certified reference materials. Metrological board and the government perform the calibration process within a predetermined time frame in order to minimize the occurrence of scales deviations. To see the results of the three balance sheets taking samples, comparing the three sample types to see the guality and guality of the balance sheet so that it will clear the balance sheet efficiently and inefficiently.